HAPUSNYA UTUSAN GOLONGAN DALAM UNDANG-UNDANG DASAR 1945 DAN DAMPAK HUKUMNYA TERHADAP REPRESENTASI KETERWAKILAN - Marsudi Dedi Putra; Regitha Putri Erlanha (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
One unique characteristic of Indonesia's representation is marked by the existence of the Utusan Group. However, after the amendment to the 1945 Constitution, the existence of Group Representatives was removed, thus affecting the institutional structure of the People's Consultative Assembly. The problems in this article are (1) What is the legal basis for the abolition of Group Representatives from the state institution of the People's Consultative Assembly?, (2) What is the legal impact of the abolition of Group Representatives on the representation of representatives in the state institution of the People's Consultative Assembly? Legal research that uses normative juridical. Research results: (1) The argument for the abolition of Utusan Golongan is because it is not fully effective in reflecting the interests of society at large, there is a tendency for Utusan Golongan to be used as a tool by the government to strengthen power, not as a pure means of group representation, and simplifying institutional structures. (2) The legal impact of eliminating Group Envoys from the MPR structure has changed the meaning of popular sovereignty. As a result, the existence of the MPR as the incarnation of all the people becomes closer to the incarnation of a political party. Key words: group delegates, 1945 constitution, legal impact, representative representation